MAHASISWA DAN KEPUTUSAN MEMILIH JURUSAN (ANALISIS KUANTITATIF PADA MAHASISWA KPI IAIN SURAKARTA TAHUN 2017/2018) - Agus Sriyanto (al-Balagh : Jurnal Dakwah dan Komunikasi, 2018)
Students certainly have a number of separate considerations in choosing a college and its majors to be taken. Including the variety of factors that influence the decision to choose. For this reason, a research is needed on what factors influence students in choosing a department in college. The research was conducted at the Islamic of Communication and Broadcasting Department (KPI) of the Theology and Da'wah Faculty of IAIN Surakarta in 2017/2018. Based on the results of the FGD, the desire of students to enter KPI was because of the motivation, promotion and encouragement of parents, and the influence of friends. With quantitative descriptive method, this study uses respondents as well as a sample of 158 students. Data collection is done by distributing questionnaires, library studies, and interviews to complete the data. Data analysis was carried out through validity and reliability, homogeneity, normality, linearity, and ended with multiple regression tests.